The contribution of epiphyton to the primary production of tropical floodplain wetlands. (21st April 2017) - Adame, Maria F.; Pettit, Neil E.; Valdez, Dominic; Ward, Doug; Burford, Michele A.; Bunn, Stuart E.
Abstract: Tropical floodplains are one of the most productive ecosystems on earth. Studies on floodplain productivity have primarily focused on trees and macrophytes, rather than algae, due to their greater biomass. However, epiphyton—algae and bacteria attached to the submerged portion of aquatic macrophytes—is a major source of energy in many tropical floodplains. Epiphyton productivity rates are unknown for most tropical floodplain wetlands, and spatial variability is not well understood. In this study, we measured primary productivity of epiphyton in Kakadu National Park in northern Australia. We estimated the relative contribution of epiphyton to aquatic production (epiphyton,  + phytoplankton + macrophytes). We sampled sites dominated by different macrophyte structural types: vertical emerging grasses, horizontal emerging grasses, submerged macrophytes, and macrophytes with floating leaves. Epiphyton productivity was highly influenced by the structural type of the macrophyte. Highest potential productivity per weight was measured from epiphyton growing on macrophytes with floating leaves and horizontal grasses (1.52 ± 0.53 and 1.82 ± 0.61 mgC/dw g epiphyton/h, respectively) and lowest in submerged macrophytes and vertical grasses (0.57 ± 0.26 and 0.66 ± 0.47 mgC/dw g epiphyton/h, respectively). When considering the areal biomass of the macrophyte and the amount of epiphyton attached, epiphyton on horizontal grasses and submerged macrophytes had productivity values approximately ten times higher (45–219 mgC/m 2 /d) compared to those on vertical grasses and macrophytes with floating leaves (2–18 mgC/m 2 /d). Epiphyton contributed between 2 to 13 percent to the aquatic production of these tropical floodplain wetlands.